Peranan Lembaga Pemasyarakatan Dalam Pelaksanaan Prinsip-Prinsip Pemasyarakatan (Studi Di Lp Pemuda Kelas Ii B Plantungan Kendal) - Istyana, Rhezky Nastha, Hartanto, S.H., M.Hum, Kuswardani, S.H., M.Hum (2016)
The prison system is based on deterrence is no longer appropriate to the concept of humanity, and need a concept based on human development, namely the correctional system which the guidelines are based on the principles of correctional services. This study aims to determine the background of the formation of philosophical, historical, sociological, and juridical of LP Youth Class IIB Plantungan Kendal, to know the steps taken by the Prison Officers in the implementation of the principles of correctional, and to determine the LP constraints faced in the implementation of the principles of correctional services. The research method used juridical empirical approach which is descriptive. Using this type of primary data and secondary data. Techniques of data collection used through the study of literature, documentation, field of study , questionnaires and interview. By using qualitative data analysis. The results showed that Correctional Institution have a role in socializing inmates/students through coaching saw prisoners as creatures of God, Individual and community members. This is the meaning of the cage to the studio in order to establish an independent human being.